Fungsi Administrasi Keuangan Pada Badan Pengelolaan Keuangan dan Aset Daerah Kantor Gubernur Sulawesi Tengah - Zainuddin Zainuddin; Ari Putra; Isbon Pageno (Jurnal ADMINISTRATOR, 2021)
The purpose of this study was to analyze the administrative function of the Regional Financial and Asset Management Agency of the Central Sulawesi Governor's Office, the number of informants in this study was 5 (five) people who were leaders and staff. The method used in this research is qualitative. The data collected in this study are primary data and secondary data. Primary data were obtained through interviews with informants related to the research. Interviews were conducted using interview guidelines and interviews conducted in this study to obtain qualitative information that can strengthen qualitative analysis. The results showed that the administrative function of the Regional Financial and Asset Management Agency of the Central Sulawesi Governor's Office was running well, but there were still obstacles where the employees who were placed were not in accordance with their expertise or knowledge, and needed improvements in organization and planned supervision.